2019
DOI: 10.1016/j.scitotenv.2018.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Are secondary forests second-rate? Comparing peatland greenhouse gas emissions, chemical and microbial community properties between primary and secondary forests in Peninsular Malaysia

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
54
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 77 publications
12
54
6
Order By: Relevance
“…As a consequence, we speculate that the significant relationships between redox potential and soil moisture and a variety of PLFA and GDGT biomarker abundances mean that seasonal changes in precipitation will influence on community structure in this ombrotrophic peatland, with potential consequences for GHG emissions. This has been previously demonstrated to be the case in temperate peatlands, with significant changes in microbial community structure with changes in water table depth (Zhong et al 2015), and has recently been reported in two tropical peatlands in Malaysia (Dhandapani et al 2019).…”
Section: Environmental Regulation Of Microbial Community Structuresupporting
confidence: 56%
See 2 more Smart Citations
“…As a consequence, we speculate that the significant relationships between redox potential and soil moisture and a variety of PLFA and GDGT biomarker abundances mean that seasonal changes in precipitation will influence on community structure in this ombrotrophic peatland, with potential consequences for GHG emissions. This has been previously demonstrated to be the case in temperate peatlands, with significant changes in microbial community structure with changes in water table depth (Zhong et al 2015), and has recently been reported in two tropical peatlands in Malaysia (Dhandapani et al 2019).…”
Section: Environmental Regulation Of Microbial Community Structuresupporting
confidence: 56%
“…Previous studies in tropical soils and peats have noted that microbial community structure and abundance can exhibit a tendency towards seasonality (Dhandapani et al 2019;Smith et al 2018). Tropical peatlands are subject to distinct wet and dry seasons which can exert a strong influence on water table height in particular, altering the balance between oxic and anoxic processes (Wright et al 2013b).…”
Section: Environmental Regulation Of Microbial Community Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Gram-negative relative abundance positively correlated with volumetric moisture. Similar correlations were also reported by Dhandapani et al (2019b), where primary peat forest with above surface water table, was dominated by Gram-negative bacteria.…”
Section: Microbes Under Different Land-use Typessupporting
confidence: 88%
“…The Malaysian oil palm and pineapple intercropping site is located in Selangor State, approximately 14 km from the west coast of Peninsular Malaysia (3°2 5 0 20.6 00 N, 101°19 0 56.6 00 E). The site is surrounded by recently planted (2014) 2nd generation oil palm mono-cropping and is drained by two drainage ditches along the borders at opposite sides of the site (Dhandapani et al 2019b). During sampling the site was not flooded, although the peat was moist, with high gravimetric moisture content.…”
Section: Study Sitesmentioning
confidence: 99%